Remarkable photocatalytic degradation of Remazol Brilliant Blue R dye using bio-photocatalyst ‘nano-hydroxyapatite’ - Sumayya Begum; Vijaykiran N Narwade; Devidas I Halge; Suhas M Jejurikar; Jagdish W Dadge; Subas Muduli; Megha P Mahabole; Kashinath A Bogle (Materials Research Express, 2020)
Nanostructured bio-photocatalyst hydroxyapatite (HAp) was synthesized by a simple and productive wet chemical precipitation method to explore the photocatalytic performance of the material for degradation of Remazol Brilliant Blue R (RBBR) dye. Wet chemically synthesized nano-HAp was characterized through x-ray diffraction, Transmission electron microscope, scanning electron microscope, N _2 -adsorption–desorption, thermo gravimetric analyzer, Fourier transform infrared and UV–vis absorption techniques. Photocatalytic degradation of RBBR under ultraviolet irradiation was examined and ∼80% degradation was achieved in 120 min by using nano-HAp. The photocatalytic degradation followed Parabolic Diffusion kinetics. Fast degradation kinetics and removal of RBBR dye was achieved by nano-HAp due to modification of surface entities leading to suppression of photo-generated electron-hole recombination. This makes nano-HAp a remarkable bio-photocatalyst material for removing dyes from water.